The military and liberal society societal-military relations in Western Europe - Kucera, Tomas (Cass military studies, 2018)
This book describes to what extent and in what ways the military policies of Western European societies are determined by liberal ideology. The book addresses a wide variety of issues affected by liberal ideology, including conscription, conscientious objection, military mission, military ethics and the professional identity of soldiers. This book will be of much interest to students of civil-military relations, military sociology, Western European politics, security studies and IR.